APAKAH KEBERAGAMAN GENDER MEMODERASI PENGUNGKAPAN ESG DAN KINERJA PERUSAHAAN? - Lestari, Widya; Widiastuty, Erna (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study aims to examine the moderating role of gender diversity in the impact of ESG on firm performance. This research uses a sample of financial sector companies listed on the Indonesia Stock Exchange for 2012-2023. The sampling method applied is purposive sampling, resulting in 74 firm-year observations. The dependent variables in this study are firm performance, measured by accounting performance (ROA and ROE) and market performance (Tobin's Q). The independent variable is ESG disclosure, measured using ESG scores from the Datastream. This study also incorporates gender diversity as a moderating variable, measured by the proportion of females on the board of directors. Secondary data sources come from Datastream and company annual reports. The research results provide empirical evidence that gender diversity does not moderate the effect of ESG disclosure on company performance on ROE and Tobin's Q. However, gender diversity moderates ESG disclosure on company performance when proxied by ROA. This research implies that the proportion of female Board of Directors in the company strengthens corporate governance, improves the company's reputation, and increases the effectiveness of decision-making. On the other hand, it now considers non-financial information such as ESG and gender diversity when making investment decisions.